With Their Back to the Future: Will Past Earnings Trigger the Next Crisis? - Jonathan Nitzan; Shimshon Bichler (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
The U.S. stock market is again in turmoil. After a two-year bull run in which share prices soared by nearly 50 per cent, the market is suddenly dropping. Since the beginning of 2018, it lost nearly 10 per cent of its value, threatening investors with an official `correction' or worse. As always, there is no shortage of explanations. Politically inclined analysts emphasize Trump's recently announced trade wars, sprawling scandals and threatening investigations, as well as the broader turn toward `populism'; interest-rate forecasters point to central-bank tightening and china's negative credit impulse; quants speak of breached support lines and death crosses; bottom-up analysts highlight the negative implications of the Face-book/Cambridge Analytica debacle for the `free-data' business model; and top-down fundamentalists indicate that, at near-record valuations, the stock market is a giant bubble ready to be punctured. And on the face of it, these explanations all ring true. They articulate various threats to future profits, interest rates and risk perceptions, and since equity prices discount expected risk-adjusted future earnings, these threats imply lower prices. But there is one little problem. Unlike their pundits, capitalists nowadays tend to look not forward, but backward: instead of matching asset prices to the distant future, they fit them to the immediate past.
Keywords: P16; G01; 330; asset pricing; capitalization; capitalized power; major bear markets; stock market; systemic fear